2021
DOI: 10.3390/microorganisms9040767
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomic Investigation of Increasing Fluoroquinolone Resistance among Belgian Cases of Shigellosis between 2013 and 2018 Indicates Both Travel-Related Imports and Domestic Circulation

Abstract: Shigellosis is an acute enteric infection caused mainly by the species Shigella flexneri and Shigella sonnei. Since surveillance of these pathogens indicated an increase in ciprofloxacin-resistant samples collected in Belgium between 2013 and 2018, a subset of 148 samples was analyzed with whole genome sequencing (WGS) to investigate their dispersion and underlying genomic features associated with ciprofloxacin resistance. A comparison between observed phenotypes and WGS-based resistance prediction to ciproflo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Ciprofloxacin resistance is not only limited to the mobile qnrS gene. In Belgium in similar years as for this study, chromosomal mutations in the Shigella gyrA and parC have been reported to contribute to rising ciprofloxacin resistance [ 44 ]. In the ESBL-positive Shigella isolates of this study, 51/100 had a point mutation in gyrA and/or parC , with gyrA p.S83L and p.D87G and parC p.S80I being the most common mutations (Table S9).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ciprofloxacin resistance is not only limited to the mobile qnrS gene. In Belgium in similar years as for this study, chromosomal mutations in the Shigella gyrA and parC have been reported to contribute to rising ciprofloxacin resistance [ 44 ]. In the ESBL-positive Shigella isolates of this study, 51/100 had a point mutation in gyrA and/or parC , with gyrA p.S83L and p.D87G and parC p.S80I being the most common mutations (Table S9).…”
Section: Resultsmentioning
confidence: 99%
“…sonnei and S. flexneri was caused by a combination of domestic circulation and international travel [44]. In contrast to bla CTX-M genes, ciprofloxacin resistance is mostly linked to chromosomal point mutations and only in a few cases by the mobile qnr gene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation